(3x-6)/(2)=x-2

Simple and best practice solution for (3x-6)/(2)=x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-6)/(2)=x-2 equation:



(3x-6)/(2)=x-2
We move all terms to the left:
(3x-6)/(2)-(x-2)=0
We get rid of parentheses
(3x-6)/2-x+2=0
We multiply all the terms by the denominator
(3x-6)-x*2+2*2=0
We add all the numbers together, and all the variables
(3x-6)-x*2+4=0
Wy multiply elements
(3x-6)-2x+4=0
We get rid of parentheses
3x-2x-6+4=0
We add all the numbers together, and all the variables
x-2=0
We move all terms containing x to the left, all other terms to the right
x=2

You can always share this solution

See similar equations:

| (100-5x)/40=x | | (x?1)(2x?3)=0 | | 3(7x-20)=36 | | 2x+-3=-1x+-6 | | x=8+3(10) | | -8+3(0)=x | | 95=-5+33x | | 940200-x=0.1x | | x(-2x+18)^2=0 | | 12/20=m/50 | | 2(x-5)-x=29 | | A-5b=8(3,-1) | | 4(3x-6)=6x-2 | | .66x=-12 | | 19+b=5.7 | | -30+2y=56 | | 2-+4n=-5-3n | | 2+10x=-34-x | | 2+10x=34-x | | 4w-12=-48 | | 4*3^x+1-9^x=27 | | -2(x-6)=14 | | 4*3^x+1-9x=27 | | 9x-1633x=20 | | -3x^2+3-8x=0 | | (x+9)2=9 | | 23=5-t | | ?2(3x?4)?x?3=33 | | t2-7t-8=0 | | 4(2x+1)-2x=-8 | | 0.25x+0.20(100-x)=21 |

Equations solver categories